Profiling Digital Health Literacy in Virus-Focused Biology Learning among Indonesian Senior High School Students - Kharomah, Sindi; Zubaidah, Siti; Susanto, Hendra; Fuad, Iwan Hadiqul (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2026)
This study profiled digital health literacy (DHL) among senior high school students in virus-focused biology learning and examined whether total DHL scores differed by gender. A quantitative descriptive survey was conducted with 64 Grade 12 students from two classes at a public senior high school in Malang, East Java, Indonesia. Participants were selected through convenience sampling. DHL was measured using an Indonesian adaptation of the Digital Health Literacy Instrument. The instrument comprised 12 items across four dimensions—Information Searching, Self-Generated Content, Evaluating Reliability, and Determining Relevance—rated on a five-point Likert scale. The overall internal consistency of the adapted instrument in the main sample was α = 0.659. Data were analyzed using descriptive statistics, an independent-samples t-test, effect-size estimation, and a Mann–Whitney U sensitivity analysis. Based on the study-specific descriptive thresholds, students’ overall DHL was predominantly classified as problematic (M = 41.20, SD = 6.69): 17.19% were classified as inadequate, 70.31% as problematic, and 12.50% as sufficient. Information Searching had the highest mean score, whereas Evaluating Reliability had the lowest. No statistically significant difference was found between male and female students, t(62) = 0.051, p = 0.959, with a negligible effect size (Cohen’s d = 0.013). These findings indicate that students perceived greater ease in locating digital health information than in evaluating its credibility and evidentiary quality. Virus-focused biology instruction should therefore provide explicit opportunities for source evaluation, cross-source verification, and evidence-based interpretation of digital health information.